FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR DI BEI - Sari, Ita Puspita; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the factors which influence income smoothing on companies which are listed in Indonesia Stock Exchange. The variables are firm size, profitability, financial leverage, and tax. Income smoothing has been carried out by using Eckel index calculation. This research is a quantitative research and the population is all manufacturing companies which are listed in Indonesia Stock Exchange in 2011- 2015 periods. The research sample selection has been done by using purposive sampling and based on the result of the Eckel index calculation, 17 companies (85 firm years) has met the criteria as the research samples. The analysis technique has been done by using multiple linear regression analysis and the SPSS 20. The result of the test with its significance level of 5% shows that: 1) Size does not give any influence to the income smoothing, 2) Return on Assets give positive influence to the income smoothing, 3) Debt to Equity Ratio does not give any influence to the income smoothing, and 4) Effective Tax Ratio give positive influence to the income smoothing.Keywords: Income smoothing, firm size, profitability, financial leverage.